About Nuclear Resonant Reaction Analysis for Hydrogen Investigations in Amorphous Silicon. (December 2015) - Gerke, Sebastian; Becker, Hans–Werner; Rogalla, Detlef; Hahn, Giso; Job, Reinhart; Terheiden, Barbara
Abstract: Nuclear Resonant Reaction Analysis (NRRA) is a common method detecting the nearsurface hydrogen distribution of a sample in a depth of up to a few microns. The mass density and related stopping power of a hydrogenated amorphous silicon (a-Si:H) layer depends on the hydrogen content. Correct hydrogen depth profiles are calculated considering the effective ion beam stopping crosssection as well as the related stopping power of the investigated film. The consideration of the local hydrogen concentration is important to avoid misinterpretations of the hydrogen distribution regarding profile depth. Therefore, stopping powers have to be considered carefully when interpreting hydrogen depth profiles especially of films that exhibit variations in hydrogen concentration. Moreover, further investigations like morphology dependent changes of the effective stoppingcross section are not possible without correctly calculated hydrogen depth profiles. Here the correct way is presented how to consider the embedded hydrogen of an a-Si:H layer when calculating absolute depth information of a NRRA measured hydrogen depth profile.